The relative contributions of each subset of ocular infiltrated cells in experimental choroidal neovascularisation. Issue 9 (17th August 2004) - Tsutsumi-Miyahara, C; Sonoda, K-H; Egashira, K; Ishibashi, M; Qiao, H; Oshima, T; Murata, T; Miyazaki, M; Charo, I F; Hamano, S; Ishibashi, T
Abstract : Aim: Choroidal neovascularisation (CNV) is a major cause of blindness in adults. The aim of this study was to investigate the role of infiltrating cells in the development of experimental CNV. Methods: CNV was induced in C57BL/6 (B6) mice by laser photocoagulation (PC). After PC, the numbers of each subset of infiltrated cells were analysed by flow cytometry at multiple time points. Each subset (except for macrophages) was depleted by the specific antibodies in vivo. Thereafter, the area of CNV was compared between the control B6 mice and the specific antibody treated mice 7 days after PC. The CNV formation in neutrophil depleted CC chemokine receptor-2 (CCR2) knockout mice was also examined to minimise the effects of macrophages. Results: In the early phase of CNV formation, a large number of neutrophils and macrophages infiltrated to the eyes. Natural killer (NK) cells and T lymphocytes were barely detected while no B lymphocytes were detected. The CNV areas did not significantly change compared between the control B6 mice and the specific antibody treated mice. However, the neutrophil depleted CCR2KO mice resulted in a reduction of CNV. Conclusion: Although lymphocytes and NK cells had little effect on CNV formation, neutrophils partially contributed to CNV in the absence of macrophages.